Assess the Using and Efficacy of Fatigue Reducing Strategies in Patients Referred to Multiple Sclerosis Association of IRAN - S Faghihzadeh; A Nikbakht Nasrabadi; SH Basampour; F Monjazebi (Tehran University of Medical Sciences, 2005)
Background & Aim: Multiple sclerosis (MS) is characterized by a broad spectrum of physical and psychological impairments. Fatigue is a common and disabling symptom for individuals with MS 75%-90% of individuals with MS reported problems with fatigue. They describe fatigue as a frustrating and overwhelming symptom that can be disabling. Methods & Materials: Assessing the usage and efficiencies of fatigue reducing strategies in patients referred to multiple sclerosis association of IRAN. This is a cross-sectional survey study of 100 patients who were selected randomly. The method of collecting data was by asking and answering and the research tool was a questionnaire. The questionnaire was prepared in four parts. Part one included the disease and demographic questions. Part two included Fatigue Severity Scale (FSS). Part tree included Fatigue Reducing Strategies and part four included Fatigue Relief Scale. The data were collected in one stage, and analyzed with SPSS software. To analyze the data, descriptive and inferential statistical methods (fisher exact test, chi square test, correlation coefficient, meant, standard deviation) have been used. Results: The Findings of this study represented that the majority of subjects (63%) were suffering of severe fatigue symptom. The most frequently used strategies to relive fatigue were lie down (51%), watching TV (30%), frequent rest (28%) and sitting without doing any thing (28%). But the most effective strategies were sleeping (8.17), daily nap (8.4), take a shower with lukewarm water (7.25), avoiding heat (7.16), exercising (7.14), praying (7.0) and socialization (7.0). Results also showed that fatigue have been affected by some variables such as education level, having child, number of children, job status, daily working hours, dwelling place and time of bed-ridden. Findings also suggested that all strategies will be useful when the highest level of fatigue has been experienced (p=0.532, r=-0.063). Conclusion: The most common strategies were not necessarily the most effective ones. Most frequently used strategies were included sleeping, napping, warm water bathing, heat avoidance, and exercising. However more physically active strategies such as exercise and socializing were more effective strategies. The patients should be suggested that to try variety of strategies such as walking and exercising besides sleeping and resting to relive the fatigue. Patients should be instructed to monitor the intensity of their fatigue and also be encouraged to maintain that level of activity which is in balance with efficient rest period.